Collaborative professional development for distributed teacher leadership towards school change. (27th May 2017) - Sales, Auxiliadora; Moliner, Lidón; Francisco Amat, Andrea
ABSTRACT: Professional development that aims to build school change capacity requires spaces for collaborative action and reflection. These spaces should promote learning and foster skills for distributed leadership in managing school change. The present study analyses the case of the Seminar for Critical Citizenship (SCC) established by teachers of infant, primary, secondary and higher education to experiment with and share innovative practices. A focus group was formed first to identify which factors SCC participants perceived as influencing the development of this leadership for change, and second, to verify whether the SCC offers a space where the development of distributed leadership is promoted. We find that while it enables a network for collaboration, egalitarian dialogue and empowerment, certain tensions persist between theory and practice, and in attitudes towards innovation and school culture.